2015
DOI: 10.1016/j.plefa.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Robust measurement of vitamin A status in plasma and blood dried on paper

Abstract: After the embargo period via non-commercial hosting platforms such as their institutional repository  via commercial sites with which Elsevier has an agreement In all cases accepted manuscripts should: link to the formal publication via its DOI  bear a CC-BY-NC-ND license -this is easy to do, click here to find out how  if aggregated with other manuscripts, for example in a repository or other site, be shared in alignment with our hosting policy  not be added to or enhanced in any way to appear more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…A recent study reported that adding chelators (such as EDTA) to the DBS papers increased correlations between stored DBS samples and venous blood control samples markedly ( r > 0.97) [ 43 ]. Similar improvement was also observed when ascorbic acid was added to DBS filters and during extraction, to improve the stability of vitamin A [ 105 ].…”
Section: Methodological Challenges and Refinement In Lipid Profiling mentioning
confidence: 56%
See 1 more Smart Citation
“…A recent study reported that adding chelators (such as EDTA) to the DBS papers increased correlations between stored DBS samples and venous blood control samples markedly ( r > 0.97) [ 43 ]. Similar improvement was also observed when ascorbic acid was added to DBS filters and during extraction, to improve the stability of vitamin A [ 105 ].…”
Section: Methodological Challenges and Refinement In Lipid Profiling mentioning
confidence: 56%
“…However, there exists some controversy on the efficacy of sampling and extraction techniques [ 114 ]. A recent paper obtained a high correlation ( r = 0.97) between venous blood and DBS samples from healthy subjects ( n = 24) using acidic extraction [ 105 ]. Similar results were demonstrated 30 years ago, where the loss of vitamin A in serum samples was eliminated when adding ascorbic acid before extraction [ 115 ].…”
Section: Dbs Profiling Of Vitamins a And Dmentioning
confidence: 99%
“…Therefore, the PLs, due to their lipophilic character, were likely not co-extracted with the RBP complex and hence, did not interfere with the analysis of retinol. As retinol is sensitive to oxidation, extraction solvents contained antioxidants such as ascorbic acid (AA), diethylenetriamine pentaacetic acid (DTPA), butylated hydroxytoluene (BHT) or hydroquinone (29,(47)(48)(49)(50).…”
Section: Sample Preparationmentioning
confidence: 99%
“…This approach is not compatible with the direct application of a drop of blood from the fingertip onto filter paper. As an alternative, Huang et al spiked increasing concentrations of retinol standard solution to already prepared and dried DBSs, after which the spiked spots were dried (49).…”
Section: Endogenous Analytesmentioning
confidence: 99%
“…Diagnosis of recent alcohol uptake LC-MS/MS 20 14 Fluoxetine, norfluoxetine, reboxetine and paroxetine TDM, toxicological analysis and PK studies NICI-MS-MS 21 15 Gabapentine Preclinical and clinical PK studies LC-MS/MS 22 16 Gemifloxacin Preclinical PK studies HILIC with fluorescence detector 23 17 Linezolid TDM LC-MS/MS 24 18 Losartan Preclinical PK studies LC-MS/MS 25 19 Methadone TDM HPLC 26 20 Metoprolol Preclinical, clinical PK and doping studies LC-MS/MS 27 21 Metronidazole PK/PD studies in neonatal patients HPLC 28 22 Nevirapine and Efavirenz TDM LC-MS/MS 29 23 Nifedipine Photo-degradation experiments LC-MS/MS 30 24 Opiates, cocainics and amphetamines Illicit drugs determination in suspected cases of driving under the influence of drugs LC-MS/MS 31 25 Paclitaxel Preclinical PK studies LC-MS/MS 32 26 Propranolol PK studies in neonates or young infants LC-MS/MS 33 27 Quinine and 3-hydroxyquinine Clinical PK studies HPLC with fluorescence detection 34 28 Ranitidine TDM in pediatrics samples LC-MS/MS 35 29 Sulfadoxine and pyrimethamine TDM and epidemiological studies HPLC-UV 36 30 Tacrolimus, sirolimus, everolimus and cyclosporin A TDM LC-MS/MS 37 31 Vincristine Clinical pharmacological studies LC-MS/MS 38 32 Zidovudine Monitoring of zidovudine therapy among HIV-infected pregnant mothers and their newborns RIA 39 Filter Paper used in DUS: Whatmann 903 neonatal cards with 13 mm diameter discs and Whatmann no. 903 filter paper are used in DUS.…”
mentioning
confidence: 99%